Combination of High-Dose Intravenous Immunoglobulins and Itraconozole in Treating Chronic Mycotic Demyelinating Optic Neuritis - Andrew W. Campbell; Ebere C. Anyanwu; Aristo Vojdani (The Scientific World Journal)
Mycotic demyelinating optic neuritis is a neurological disorder of the visual system caused by mycotoxins released by indoor toxic molds. Although the health effect of indoor toxic mold on the population worldwide is now one of the emerging diseases, its involvement in chronic demyelinating optic neuritis has not been reported. Most of the neurological and immunologic abnormalities associated with toxic mold mycotoxins are very difficult to treat successfully, especially neural demyelination of the central and peripheral nervous systems. This paper presents the case of a 42-year-old white female, in whom chronic demyelinating optic neuritis with persistent visual defects due to chronic exposure to toxic molds was diagnosed at the age of 34 years. In spite of all the therapeutic services given to her for over 8 years, her illness persisted and was difficult to treat. However, we successfully treated her with a combination of intravenous immune globulin (IVIG) and itraconozole (Sporanox) when all other treatment modalities failed. This is probably the first report where persistent toxic mold-induced neurological and immunologic disorders were successfully treated with a combination of itraconozole and IVIG.